Morfologiczne i anatomiczne zróżnicowanie populacji kosodrzewiny ( Pinus mugo Turra) z polskich Tatr wyrażone w cechach igieł - Pawlaczyk, Ewa; Bączkiewicz, Alina; Buczkowska, Katarzyna; Czołpińska, Magdalena; Gonera, Patrycja; Wawrzyniak, Piotr (Leśne Prace Badawcze, 2017)
The main aim of this study was to describe the variation between the populations of the dwarf mountain pine Pinus mugo Turra based on the morphological and anatomical traits of their needles, and to investigate the relationship between the observed variation and environmental conditions (altitude and substrate).Two-year-old needles were collected from 180 individuals of six populations of P. mugo growing in the Tatra Mts. Two populations were classified as dense, located at 1360–1450 m altitude, and the remaining four formed loose clusters and were situated at 1500–1650 m altitude. Four of the populations are growing on granite and two on a limestone substrate. The natural variation of 10 morpho-anatomical and 3 synthetic needle traits was measured. In addition to descriptive statistics, the analyses of variance (ANOVA) with a Tukey test and principal component analysis were computed. We also estimated Pearson correlation coefficients for the examined needle traits and altitude as well as substrate. Our results indicate that the P. mugo populations differ significantly with regard to the investigated traits for which the Trzydniowiański Wierch population was the most distinct. The observed pattern of variability is largely caused by differences in stomatal traits and these features are positive correlated with altitude. Additionally, populations growing on granite have larger values for most of the examined traits compared to populations growing on limestone.